Comparison of the Effects of Three Sulfonylureas on in vivo Insulin Action - Sato, Juichi; Ohsawa, Isao; Oshida, Yoshiharu; Fukuharu, Michitaro; Hu, Xiao Chen; Tamagawa, Tatsuo; Sato, Yuzo (Arzneimittelforschung, 2001)
To clarify the diversity in hypoglycemic actions of sulfonylureas, chronic effects of three sulfonylureas were compared on in vivo insulin-induced glucose uptake in peripheral tissues. After oral administration of glimepiride (CAS 93479-97-1), gli-benclamide (CAS 10238-21-8), gliclazide (CAS 21187-98-4), or saline as control, two-step euglycemic clamp procedures were performed. During physiological hy-perinsulinemia induced by 6 mU/kg/min insulin infusion, metabolic clearance rates (MCR) of glucose of the glimepiride-administered group (GP) significantly (p<0.01) increased to 153 % of the saline-administered group (SA). There was no significant statistical difference between the glibenclamide-administered group (GC), gliclazide-administered group (GZ) and SA. During 30 mU/kg/min clamps that lead to maximal insulin action, MCR of either GP or GC were significantly higher than those of SA (128 % and 141 %, p<0.05 and p<0.01, respectively). MCR of GZ were lower than those of GC (80 %, p<0.05), and showed no significant difference from those of SA. These data indicate that glimepiride activates insulin binding levels to a greater degree than the other two sulfonylureas, and that glibenclamide and glimepiride activate post-receptor binding mechanisms in peripheral tissues much more than gliclazide. These results suggest that hypoglycemic actions of sulfonylureas at the extra pancreatic levels vary with the nature of each reagent.
Keywords: CAS 10238-21-8; CAS 21187-98-4; CAS 93479-97-1; Glibenclamide, effect on insulin action, in vivo studies; Gliclazide, effect on insulin action, in vivo studies; Glimepiride, effect on insulin action, in vivo studies; Insulin clamp; Sulfonylureas